Ujian Nasional Sebagai Cermin Mutu Pendidikan dan Pemersatu Bangsa - Safari -- (Jurnal Pendidikan dan Kebudayaan, 2015)
The aim of this study was to answer the question whether the national examination can be a nation adhesive and UN results can reflect the quality of education. This research used survey method. The study population was the educator in Banda Aceh province of Aceh in 2014, while the sample as much as 78 respondents consisting of 24 SMAN (public senior secondary school) students and 27 MAN (public islamic senior secondary school) students, 19 teachers SMAN and MAN, 8 officials in ministry of educational culture including the principal of SMAN and MAN. Based on the results of the descriptive analysis of the results this research revealed reflected, first, respondents who had agreed UN as a nation adhesive is 79.5%, while respondents who had disagree is 20.5%. Second, respondents stated that the UN can reflect the quality of education is 59%, while respondents who said no is 41%. Based on the results of the study, it is concluded that the National Examination has become a nation adhesive and reflected the actual quality of education, although not maximized.ABSTRAKTujuan studi ini adalah menjawab pertanyaan apakah ujian nasional dapat menjadi pemersatu bangsa dan apakah hasil UN dapat mencerminkan mutu pendidikan secara nasional. Metode penelitian ini menggunakan metode survei. Populasi penelitian ini adalah pelaku pendidikan di Banda Aceh Provinsi Aceh tahun 2014, dengan sampel sebanyak 78 responden yang terdiri dari 24 siswa SMAN dan 27 siswa MAN, 19 guru SMAN dan MAN, 8 pejabat di lingkungan Dikbud termasuk kepala sekolah SMAN dan MAN. Berdasarkan hasil analisis deskriptif diperoleh hasil, pertama, responden yang menyatakan setuju UN sebagai pemersatu bangsa adalah 79,5%, sedangkan responden yang menyatakan tidak setuju adalah 20,5%. Kedua, responden yang menyatakan bahwa hasil UN dapat mencerminkan mutu pendidikan secara nasional adalah 59%, sedangkan responden yang menyatakan tidak adalah 41%. Berdasarkan hasil studi disimpulkan bahwa Ujian Nasional sudah menjadi perekat bangsa dan mencerminkan mutu pendidikan walaupun belum maksimal.